A novel murine model of differentiation-mediated cytomegalovirus reactivation from latently infected bone marrow haematopoietic cells. (24th October 2019) - Liu, Xue-feng; Swaminathan, Suchitra; Yan, Shixian; Engelmann, Flora; Abbott, Darryl Adelaide; VanOsdol, Luke Andrew; Heald-Sargent, Taylor; Qiu, Longhui; Chen, Qing; Iovane, Andre; Zhang, Zheng; Abecassis, Michael M.
Abstract : CD34+ myeloid lineage progenitor cells are an important reservoir of latent human cytomegalovirus (HCMV), and differentiation to macrophages or dendritic cells (DCs) is known to cause reactivation of latent virus. Due to its species-specificity, murine models have been used to study mouse CMV (MCMV) latency and reactivation in vivo . While previous studies have shown that MCMV genomic DNA can be detected in the bone marrow (BM) of latently infected mice, the identity of these cells has not been defined. Therefore, we sought to identify and enrich for cellular sites of MCMV latency in the BM haematopoietic system, and to explore the potential for establishing an in vitro model for reactivation of latent MCMV. We studied the kinetics and cellular characteristics of acute infection and establishment of latency in the BM of mice. We found that while MCMV can infect a broad range of haematopoietic BM cells (BMCs), latent virus is only detectable in haematopoietic stem cells (HSCs), myeloid progenitor cells, monocytes and DC-enriched cell subsets. Using three separate approaches, MCMV reactivation was detected in association with differentiation into DC-enriched BMCs cultured in the presence of granulocyte-macrophage colony-stimulating factor (GM-CSF) and interleukin 4 (IL-4) followed by lipopolysaccharide (LPS) treatment. In summary, we have defined the kinetics and cellular profile of MCMV infection followed by the natural establishment of latency in vivo in the mouse BM haematopoietic system, including the haematopoietic phenotypes of cells that are permissive to acute infection, establish and harbour detectable latent virus, and can be stimulated to reactivate following DC enrichment and differentiation, followed by treatment with LPS.